We are asked to verify the following identity:

### sec^4 x - sec^2 x = tan^4 x + tan^2 x

=> sec^4 x - sec^2 x= tan^2 x ( tan^2 x + 1)

=> sec^4 x - sec^2 x = tan^2 x ( sec^2 x)

=> sec^4 x - sec^2 x = sec^2 x -1 ( sec^2 x)

=> sec^4 x - sec^2 x = sec^4 x - sec^2 x

**The identity sec^4 x -sec^2 x = tan^4 x + tan^2 x can be verified.**

We need to verify that (sec x)^4 - (sec x)^2 = (tan x)^4 + (tan x)^2.

We know that (sin x)^2 + (cos x)^2 = 1

=> (sin x)^2 / (cos x)^2 + (cos x)^2/ (cos x)^2 = 1/(cos x)^2

=> (tan x)^2 + 1 = (sec x)^2

Starting with the left hand side:

(sec x)^4 - (sec x)^2

=> (sec x)^2[(sec x)^2 - 1]

=> [(tan x)^2 + 1][(tan x)^2 + 1 - 1]

=> [(tan x)^2 + 1][(tan x)^2]

=> (tan x)^4 + (tan x)^2

which is the right hand side.

**This proves that (sec x)^4 - (sec x)^2 = (tan x)^4 + (tan x)^2.**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now